The Role of Herpes Simplex Virus ICP27 in the Regulation of UL24 Gene Expression by Differential Polyadenylation - Hann, Louane E. (American Society for Microbiology, 1998)
Herpes simplex virus specifies two sets of transcripts from the UL24 gene, short transcripts (e.g., 1.4 kb), processed at the UL24 poly(A) site, and long transcripts (e.g., 5.6 kb), processed at the UL26 poly(A) site. The 1.4- and 5.6-kb transcripts initiate from the same promoter but are expressed with early and late kinetics, respectively. Measurements of transcript levels following actinomycin D treatment of infected cells revealed that the 1.4- and 5.6-kb UL24 transcripts have similar stabilities, consistent with UL24 transcript kinetics being regulated by differential polyadenylation rather than by differential stabilities. Although the UL24 poly(A) site, which gives rise to short transcripts, is encountered first during processing, long transcripts processed at the UL26 site are equally or more abundant; thus, operationally, the UL24 site is weak. Using a series of viral ICP27 mutants, we investigated whether ICP27, which has been suggested to stimulate the usage of weak poly(A) sites, stimulates 1.4-kb transcript accumulation. We found that accumulation of 1.4-kb transcripts did not require ICP27 during viral infection. Rather, ICP27 was required for full expression of 5.6-kb transcripts, and the decrease in 5.6-kb transcripts relative to 1.4-kb transcripts was not due solely to reduced DNA synthesis. Our results indicate that temporal expression of UL24 transcripts can be regulated by differential polyadenylation and that although ICP27 is not required for processing at the operationally weak UL24 poly(A) site, it does modulate 5.6-kb transcript levels at a step subsequent to transcriptional initiation.